Genetic mechanisms of dynamic functional connectivity density in diabetic retinopathy brains: a combined transcriptomic and resting-state functional magnetic resonance imaging study - Zhong, Yu-Lin; Liu, Hao; Huang, Xin (Frontiers in Cellular Neuroscience, 2025)
BackgroundDiabetic retinopathy (DR) is a condition characterized by fundus lesions resulting from retinal microvascular leakage and obstruction linked to chronic progressive diabetes mellitus. Previous neuroimaging research has revealed both structural and functional changes in the brains of DR patients. Nevertheless, the variations in dynamic functional connectivity density (dFCD) within the brains of DR patients, along with the underlying molecular mechanisms connected to these changes, have yet to be fully understood.MethodsForty-seven diabetic retinopathy (DR) patients and 46 healthy controls (HCs) matched for sex, age, and education were recruited for this study from the Department of Ophthalmology at the Jiangxi Provincial People’s Hospital. All subjects underwent resting-state functional magnetic resonance imaging scans to analyze the differences in dFCD between the two groups. Utilizing the Allen Human Brain Atlas, we conducted spatial correlation analyses integrating transcriptomic and neuroimaging data to pinpoint genes showing correlated expression levels with dFCD alterations in DR patients. Subsequently, we carried out gene enrichment, specific expression, and protein-protein interaction analyses.ResultsIn comparison to the HC group, the DR group exhibited significantly reduced dFCD variability in the left anterior cingulum, left superior occipital gyrus, and right postcentral gyrus. The abnormal dFCD variability is linked to 1,318 positively and 1,318 negatively associated genes, primarily enriched for biological functions such as ion channels, synapses, and cellular junctions. Specific expression analysis revealed that these genes were distinctly expressed in Purkinje neurons, cortex, and striatum brain regions. Furthermore, protein-protein interaction (PPI) analyses indicated that these positive and negative genes could organize PPI networks with the support of respective hub genes.Conclusionour study identified altered dFCD variability in brain regions linked to visual and cognitive functions in DR patients. Moreover, transcriptome-neuroimaging correlation analyses revealed a spatial association between these dFCD changes and the genes with unique functional profiles. These genes were enriched in biologically significant functions and pathways, specific to certain cells and brain areas. Our research offers novel understandings of the genetic mechanisms influencing dFCD alterations in DR.